Perencanaan SDM (Human Resource Planning) - Riyadi, Sugeng; Firdaus, Ahmad Sofwan (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Human Resource Planning (HRP) plays a strategic role in ensuring the sustainability and quality of educational institutions, particularly within the context of Islamic education. This paper examines Human Resource Planning as a systematic, continuous, and future-oriented process aimed at ensuring the availability of competent, motivated, and goal-oriented human resources aligned with institutional objectives. HRP is not merely concerned with determining workforce quantity, but also emphasizes the development of human potential as a valuable organizational asset. Drawing on the perspectives of Mondy, Werther and Davis, Handoko, and Hasibuan, this study highlights HRP as an integrated activity encompassing workforce analysis, forecasting, recruitment, development, and evaluation. The discussion further elaborates on planning the future needs of teachers, educational staff, and educational leadership. Teachers are positioned as key agents of change who must possess pedagogical competence, adaptability to technological developments, and strong moral character. Educational staff are recognized as essential supporters of institutional effectiveness, requiring technical skills, professionalism, and ethical commitment. Leadership planning is emphasized as a long-term process involving succession planning, continuous leadership development, and value-based leadership, especially within Islamic educational institutions. Moreover, this paper underscores the importance of designing job descriptions and job specifications that reflect Islamic values. In Islamic education institutions, these instruments function not only as administrative guidelines but also as moral frameworks that integrate professionalism with spirituality. Through effective HRP, educational institutions can become adaptive, ethical, and sustainable.